Culprit lesion morphology in patients with ST-segment elevation myocardial infarction assessed by optical coherence tomography. Issue 8 (December 2020) - Hansen, Kirstine Nørregaard; Antonsen, Lisbeth; Maehara, Akiko; Maeng, Michael; Ellert, Julia; Jakobsen, Lars; Ahlehoff, Ole; Thim, Troels; Veien, Karsten; Junker, Anders; Fallesen, Christian; Terkelsen, Christian Juhl; et al.
Abstract : Aims: This study sought to evaluate the incidence of ruptured plaques and nonruptured plaques (NRP) and to compare patient characteristics and detailed plaque morphology features between the two culprit types in ST-segment elevation myocardial infarction (STEMI) patients, using optical coherence tomography (OCT). Methods and results: Using OCT, the culprit lesions in patients with STEMI were assessed prior to stent implantation. The culprit lesion was categorized as ruptured plaques or NRP, and the plaque components were evaluated. Fifty-two patients (69.3%) presented with ruptured plaques and 23 (30.7%) with NRP. Patients with NRP were younger (58.0 ± 10.4 vs 64.7 ± 9.9 years, P = 0.01) and more often smokers (72.7% vs 37.1%, P = 0.001), compared to ruptured plaques. NRP contained significantly more fibrotic plaque (20.0% [interquartile range (IQR) 13.7–29.8] vs 11.3% [IQR 6.9–18.1], P = 0.005), but less lipidic plaque (44.0% ± 13.7 vs 59.3% ± 13.6, P < 0.001), less superficial [5.0% (IQR 2.8–7.5) vs 8.1% (IQR 5.7–11.0), P = 0.005] and profound macrophages [0.9% (IQR 0.0–1.7) vs 2.2% (IQR 0.9–4.7), P = 0.003]. The prevalence, numbers and lengths of thin-cap fibroatheroma (TCFA) were significantly lower in NRP, compared to ruptured plaques [47.8% vs 88.5%, 0 (IQR 0–1) vs 1 (IQR 1–2) and 0 mm (IQR 0–2.7) vs 4.5 mm (IQR 2.3–7.7), P < 0.001]. Conclusions: One-third of STEMI patients had culprit lesions without an OCT-detectable ruptured plaque. Culprit lesions with NRP contained less vulnerable plaque components, such as lipid plaque, TCFAs and macrophages compared to ruptured plaques.